Is vitamin D deficiency related to a higher risk of hospitalization and mortality in veterans with heart failure?. (February 2020) - Aparicio-Ugarriza, Raquel; Salguero, Douglas; Mohammed, Yaqub Nadeem; Ferri-Guerra, Juliana; Baskaran, Dhanya J; Mirabbasi, Seyed Abbas; Rodriguez, Alexis; Ruiz, Jorge G.
Highlights: Vitamin D deficiency is an independent risk factor for hospitalization in patients with heart failure. Frail patients with heart failure and vitamin D deficiency have an even higher risk of hospitalization. No association between mortality and vitamin D deficiency is found. Vitamin D levels should be monitored in patients with heart failure. Abstract: Objectives: 25-hydroxyvitamin D [25(OH)D] deficiency is related to an increase in cardiovascular risk but the association between low 25(OH)D and hospitalization and mortality in heart failure (HF) patients remains unclear. The objective of this study was therefore to determine whether 25(OH)D deficiency is associated with a higher risk of all-cause hospitalizations and mortality in veterans with HF, as well as the differential effect of frailty. Study design: A retrospective cohort study of veterans with HF. Main outcome: Association between 25(OH)D deficiency and risk of hospitalization and mortality. Measures: 25(OH)D status was dichotomized as deficiency (<30 ng/mL) and non-deficiency (≥30 ng/mL). A 44-item Frailty Index (FI) was constructed and used to categorize patients as non-frail (FI < .21) or frail (FI ≥ .21). The association of 25(OH)D deficiency with recurrent hospitalization was analyzed through an Andersen-Gill model and the association with mortality using Cox regression. Results: We identified 284 patients, of whom 141 (50 %) exhibited 25(OH)D deficiency (67.3 ± 10.5 years of age). The mean 25(OH)D levels in the deficiency and non-deficiency groups were 21.3 ±5.9 ng/mL and 40.9 ± 10.9 ng/mL, respectively. Over a median follow-up of 1136 days (IQR = 691), there were 617 hospitalizations (68 % in those with 25(OH)D deficiency) and 131 deaths (40 % in those with 25(OH)D deficiency). A significantly higher risk of hospitalization was found in patients with 25(OH)D deficiency: hazard ratio (HR) = 1.8 (95 % CI:1.3–2.5), p < 0.001. Frail veterans had a greater risk of hospitalization than non-frail veterans: HR = 1.7 (95 % CI:1.2–2.7), p < 0.05. Mortality did not show any significant association with 25(OH)D deficiency. Conclusions: 25(OH)D deficiency was an independent risk factor for hospitalization in patients with HF and the effect persisted in those with frailty.